The influence of competitive anxiety of Chinese elite swimmers - Zhou, Yuhang; Jin, Zhenyu; Wen, Yuhong (Frontiers in Psychology, 2024)
Background: Competitive anxiety is a common stress response in competitive environments, influencing sports performance, particularly among elite swimmers. Purpose: This study aims to examine how the characteristics of competitive anxiety impact sports performance across different phases of competitive preparation, alongside its correlation with trait anxiety. Methods: A longitudinal research design, integrating quantitative and qualitative approaches, was employed with 20 swimmers from the Chinese national swimming team participating in both the 2023 Fukuoka World Championships and the Hangzhou Asian Games. The mental readiness form-3 (MRF-3) scale was employed at four time points during the preparation period for longitudinal tracking, complemented by the trait anxiety inventory (T-AI) scale to assess trait anxiety. Results: The study identified a negative correlation between cognitive anxiety and somatic anxiety among elite swimmers, with confidence demonstrating a positive correlation. Additionally, there was a significant between trait anxiety and competitive anxiety (p< 0.05). Variations in competitive anxiety were found at different stages of the preparation cycle (F=15.074; 11.627; 19.552, p < 0.05), impacting sport performance. Conclusion: To optimize performance, tailored psychological intervention programs should be developed and implemented to address the distinct characteristics of competitive anxiety experienced by elite swimmers throughout the preparation phases.